Genotypic variability estimates of agronomic traits in secondary triploid banana ‘Matooke’ (Musa sp., AAAEA) hybrids - Tendo Ssali, Reuben; Barekye, Alex; Buregeya, Henry; Erima, Rockefeller; Namanya, Priver; Kubiriba, Jerome (African Journal of Plant Science, 2016)
Effective selection of hybrids for a trait is based on the extent of variation and heritability. This study examined yield parameters of secondary triploid ‘Matooke’ hybrids and the extent of their genetic diversity based on the traits evaluated. Eleven genotypes, including nine ‘Matooke’ hybrids and two landraces were evaluated for 12 characters in a preliminary yield trial (PYT) over three crop cycles. Plant height, bunch weight, number of standing leaves at flowering and the youngest leaf spotted with black Sigatoka symptoms showed significant interaction between genotype and crop cycle. While characters such as pseudo stem girth, number of days for fruit filling, number of hands, number of fingers on the second hand and the fruit length showed stable differences amongst these genotypes. The genotypic coefficient of variation for the characters ranged from 7.6% (finger length) to 33.5% (bunch weight); with moderate heritability estimates varying from 13.5% (pseudostem girth) to 67% (plant height). Bunch weight showed strong positive correlation with number of hands, number of fingers on the second hand, the fruit length and pseudostem girth. These results imply that breeders could select for some of these variable and ratoon stable traits in a single cycle of early evaluation trial, subsequently reducing costs, time and space in field testing.
Keywords: Genetic variation; Heritability; Expected genetic gain; Selection; Musa sp